2017
DOI: 10.1088/1674-1056/26/4/048104
|View full text |Cite
|
Sign up to set email alerts
|

Interface states study of intrinsic amorphous silicon for crystalline silicon surface passivation in HIT solar cell*

Abstract: Intrinsic hydrogenated amorphous silicon (a-Si:H) film is deposited on n-type crystalline silicon (c-Si) wafer by hotwire chemical vapor deposition (HWCVD) to analyze the amorphous/crystalline heterointerface passivation properties. The minority carrier lifetime of symmetric heterostructure is measured by using Sinton Consulting WCT-120 lifetime tester system, and a simple method of determining the interface state density (D it ) from lifetime measurement is proposed. The interface state density (D it ) measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…The current density and voltage decrease dramatically since the surface passivation deteriorates. [9,10] In order to achieve the favorable chemical passivation, the i-a-Si: H layer is required to be deposited between c-Si and a-Si: H. [11][12][13] However, because of the higher absorption coefficient of a-Si: H than that of Si, a-Si: H will significantly reduce the spectrum response, therefore leading to the decrease of J sc directly. [14,15] Besides, it is reported that each thickness increase by 10 nm can lead to the J sc decrease by 1.5 mA/cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The current density and voltage decrease dramatically since the surface passivation deteriorates. [9,10] In order to achieve the favorable chemical passivation, the i-a-Si: H layer is required to be deposited between c-Si and a-Si: H. [11][12][13] However, because of the higher absorption coefficient of a-Si: H than that of Si, a-Si: H will significantly reduce the spectrum response, therefore leading to the decrease of J sc directly. [14,15] Besides, it is reported that each thickness increase by 10 nm can lead to the J sc decrease by 1.5 mA/cm 2 .…”
Section: Introductionmentioning
confidence: 99%